Georg Wilhelm Friedrich Hegel : a propaedeutic - Hoffmann, Thomas Sören. (Critical Studies in German Idealism, 2015)
In Georg Wilhelm Friedrich Hegel - A Propaedeutic , Thomas Sören Hoffmann offers a comprehensive intellectual biography of the "master philosopher of German idealism," the last great system builder of European philosophy. All the major themes of Hegel's thought are worked through - logic and metaphysics; history and spirit; art and language; thought and nature; right, religion and science - and presented as open invitations to conversing with, to working with, indeed to thinking with the great philosopher himself. Hegel's dialectical concept of life is one key deployed by Hoffmann to throw new light on the philosopher's work and to offer resolutions of the perennial enigmas besetting and controversies surrounding it.